Poor adherence to guidelines in treatment of fragile and cognitively impaired patients with hip fracture: a descriptive study of 2,804 patients - Frandsen, Christina F; Glassou, Eva N; Stilling, Maiken; Hansen , Torben B (Acta Orthopaedica, 2021)
Background and purpose — Following a hip fracture, most patients will encounter poorer functional outcomes and an increased risk of death. Treatment-monitoring of hip frac- ture patients is in many countries done by national audits. However, they do not allow for a deeper understanding of treatment limitations. We performed a local evaluation study to investigate adherence to 7 best-practice indicators, and to investigate patient groups at risk of suboptimal treatment. Patients and methods — 2,804 patients were surgically treated for a hip fracture from 2011 to 2017 at our institution. Data regarding admission, hospital stay, and discharge was prospectively collected, and adherence to the 7 best practice indicators (nerve block, surgical delay, antibiotics, implant choice, thromboprophylaxis, mobilization, and blood trans- fusions) was analyzed. Patient groups with lower adherence were identified. Results — 34% of patients received all 7 best practice indicators after considering contraindications; in particular, nerve blocks and thromboprophylaxis displayed low adher- ence at 61% and 91% respectively. Nursing home residents and patients with cognitive impairment, multiple comorbidi- ties, or low functional levels were at risk of having a lower adherence. Interpretation — The most dependent patients with cog- nitive impairment, comorbidities, or low functional levels had lower guideline adherence. This large patient subgroup needs a higher treatment focus and more resources. Our find- ings are likely similar to those in other national and interna- tional institutions.